High strength paper production based on esterification of thermomechanical pulp fibers in the presence of poly(vinyl alcohol). Issue 3 (November 2015) - Awada, Houssein; Bouatmane, Mohamed; Daneault, Claude
Abstract: Thermomechanical pulp (TMP) fibers, generally used to produce newspapers and carton materials, have poor inter- and intra-fiber bonding contributing to low strength properties. Poly(vinyl alcohol) (PVOH) was applied as a co-additive of 1, 2, 3, 4-butanetetracarboxylic acid (BTCA), in the presence of sodium hypophosphite (SHP) as a catalyst, to esterify paper sheets based on TMP fibers. Fourier transform infrared (FTIR) spectroscopy technique was used to confirm the formation of the ester bond. The effects of curing temperature, molar mass and mass amount of the PVOH on the tensile index were investigated. The increasing of the curing temperature improved further the wet tensile index. The presence of PVOH increased both the dry and the wet tensile index of the paper sheets. The rise of both the molar mass and the mass amount of PVOH improved the tensile index.